GENEROS CUPHOCERINOS DE TAQUINIDOS CHILENOS - González, Christian R. (Acta Entomológica Chilena, 2022)
Chilean Cuphocerini Tachinid flies (Tachininae) comprises in Ihis revisión 13 genera and 31 species nationally distributed in this country from Arica (Lat. So. 18fi) down to Magallanes (Lat. So 56s) and from the Pacific to the high Andes. Allelomyia is herein described as a new monotypic genus cióse to Trichophoropsis Townsend, while Dolichostoma nigricaudum (Blanchard), from Tucumán, Argentina, is for the first time recorded from Northern Chile. Spanipalpus picturatiis and S. rubidus are described as new species, as well as Vibrissomyia concinnata, Trichophoropsis bicolor and T. coscaroni. A key to all included genera is also offered plus pardal keys to Chilean Spanipalpus Town. and Vibrissomyia Town. Group characters of the Tribe are discussed poindng out some extra limital frequent anomalies in Spanipalpus, Vibrissomyia et. al., which after further revisión of larger series of examples may eventually reveal unexpected new sinonimies. All the material referred to in this paper belongs to the Insects Collection of the Instituto de Entomología (IEUMCE) where it remain deposited together wilh types.